Bir üniversite hastanesinde çalışan hemşirelerin algıladıkları stresin somatizasyon bozukluğu ile ilişkisi - POLAT KARA, Mine (My University, 2022)
This research; This research was conducted as a relation-seeking study to determine the relationship between perceived stress levels, symptoms of somatic disorder, and perceived stress and somatization disorder of nurses working in a foundation university hospital. The research was carried out with 99 nurses working at a Foundation University Hospital on the European Side of Istanbul between 20-26 December 2021. Socio-Demographic Characteristics Information Form, Perceived Stress Scale and Somatization Scale were used to collect data. Descriptive statistical analysis (mean, standard deviation, frequency), Mann-Whitney U test, Kruskal Wallis test and Spearman correlation analysis were used in the evaluation of the data. In the study, the total mean score of the Perceived Stress Scale of the nurses was 17,84±3,19, the mean of the Perceived Stress sub-dimension score was 10,34±3,68, the mean of the Perceived Coping sub-dimension was 7,49±1,49, and the mean of the Somatization Scale was 13,41±5,34. It was found 41±5,34. Perceived Coping sub-dimension mean score of the nurses who are somewhat satisfied and satisfied with their profession was found to be statistically significantly higher than the nurses who were not satisfied with their work. A very weak positive correlation was found between the age of the nurses and the Perceived Stress Scale Perceived Stress sub-dimension and a weak positive correlation between the Perceived Stress Scale total score. A weak positive correlation was found between the Perceived Stress Scale Perceived Stress sub-dimension and the total score and the Somatization Scale. . A weak negative correlation was found between the Perceived Coping subscale and the Somatization Scale. As a result of the research, it was determined that the nurses participating in the research experienced moderate stress and that the nurses who were satisfied with the nursing profession had higher levels of coping with stress. It was determined that as the age of the nurses increased, their perceived stress levels increased. It was determined that as the perceived stress level of the nurses increased, somatization symptoms increased, and somatization symptoms decreased as the levels of coping with stress increased. In line with these results, in order to increase nurses' coping with stress, it can be ensured that nurses' levels of coping with stress and therefore the quality of nursing care can be increased by organizing stress coping trainings in institutions. In addition to these, in order to increase the professional satisfaction of nurses, it is important that nursing organizations work at the policy level as well as improving the working conditions of the institutions.
Bu araştırma; bir vakıf üniversitesi hastanesinde çalışan hemşirelerin algıladıkları stres düzeylerini, somatik bozukluk belirtilerini ve algılanan stres ile somatizasyon bozukluğu arasındaki ilişkiyi belirlemek amacıyla ilişki arayıcı bir araştırma olarak gerçekleştirildi. Araştırma 20-26 Aralık 2021 tarihleri arasında İstanbul'da Avrupa Yakasında bir Vakıf Üniversitesi Hastanesinde çalışan 99 hemşire ile gerçekleştirildi. Verilerin toplanmasında Sosyo-Demografik Özellikler Bilgi Formu, Algılanan Stres Ölçeği ve Somatizasyon Ölçeği kullanıldı. Verilerin değerlendirilmesinde tanımlayıcı istatistiksel analizler (ortalama, standart sapma, frekans), Mann-Whitney U testi, Kruskal Wallis testi ve Spearman korelasyon analizi kullanıldı. Araştırmada hemşirelerin Algılanan Stres Ölçeği toplam puan ortalaması 17,84±3,19, Algılanan Stres alt boyutu puan ortalaması 10,34±3,68 Algılanan Baş Etme alt boyutu puan ortalaması 7,49±1,49 ve Somatizasyon Ölçeği puan ortalaması 13,41±5,34 bulundu. Mesleğinden biraz memnun ve memnun olan hemşirelerin Algılanan Baş Etme alt boyutu puan ortalaması, çalışmaktan memnun olmayan hemşirelere göre istatistiksel açıdan anlamlı derecede yüksek bulundu. Hemşirelerin yaşı ile Algılanan Stres Ölçeği Algılanan Stres alt boyutu arasında pozitif yönde çok zayıf ilişki ve Algılanan Stres Ölçeği toplam puanı arasında pozitif yönde zayıf ilişki bulundu. Algılanan Stres Ölçeği Algılanan Stres alt boyutu ve toplam puanı ile Somatizasyon Ölçeği arasında pozitif yönde zayıf ilişki bulundu. Algılanan Baş Etme alt ölçeği ile Somatizasyon Ölçeği arasında negatif yönde zayıf ilişki bulundu. Araştırma sonucunda araştırmaya katılan hemşirelerin orta düzeyde stres deneyimledikleri ve hemşirelik mesleğinden memnun olan hemşirelerin stresle baş etme düzeylerinin daha yüksek olduğu saptandı. Hemşirelerin yaşı arttıkça algılanan stres düzeylerinin arttığı belirlendi. Hemşirelerin algıladıkları stres düzeyleri arttıkça, somatizasyon belirtilerinin arttığı, stresle baş etme düzeyleri arttıkça somatizasyon belirtilerinin azaldığı saptandı. Bu sonuçlar doğrultusunda hemşirelerin stresle baş etmelerini arttırmak için kurumlarda stres ile baş etme eğitimlerinin düzenlenmesi ile hemşirelerin stresle baş etme düzeyleri, dolayısıyla da hemşirelik bakım kalitesinin yükseltilmesi sağlanabilir. Bunların yanı sıra hemşirelerin mesleki memnuniyetlerinin arttırılması için kurumların çalışma koşullarını iyileştirmesinin yanı sıra, hemşirelik örgütlerinin de politikalar düzeyinde çalışmalar yapması önemlidir.
Keywords: hemşire; nurse; stres; somatization disorder; somatizasyon bozukluğu